The Factors Influencing Chinese Consumer Purchase Intention through Webcast Transaction - Li, Jia Ning; Traiwannakij, Surachai; Viwathpongpan, Kowin (Proceedings of International Conference of Graduate School on Sustainability, 2024)
Although live webcast transactions have only emerged for a few years, they have rapidly grown from obscurity to near-ubiquity. Webcast transactions have significantly influenced the economy and society in a very short period. E-commerce platforms are the root of live webcast transactions, and as the leader of live webcast transactions, e-commerce anchors are undoubtedly the most influential. Since 2020, live webcast transactions have become the choice of many merchants. The influx of diversified funds and entities has led to the explosion of the "live streaming with goods" industry, but many problems and loopholes have also emerged. The e-commerce platform bears the brunt of the problem and deserves special attention due to its essential and critical position in live trading. This paper aims to investigate the factors influencing Chinese consumer purchase intention based on three aspects: demographic factors, consumer behavioral factors, and marketing mix 7ps factors. The quantitative method based on questionnaires is applied. Descriptive statistics such as frequency, percent frequency, mean, and standard deviation are introduced. Various inferential statistical methods are used to test the hypothesis, particularly the Independent Sample t-test, the One-way ANOVA, the Two-way ANOVA, and the Multiple Regression analysis. The results obtained from the study indicate that differences in Age, Educational Level, and Monthly Income generate differences in Consumer Purchase Intention when the Two-way ANOVA Statistics are applied. Regarding Consumer Behavior, it is evident that differences in Money Spent, Purchasing Reasons, and Terms of Payment generate differences in Consumer Purchase Intention, confirmed by the One-way ANOVA statistics. The results of the Multiple Semi-Log Linear Regression Analyses show that there is a significant positive impact of Marketing Mix 7Ps (Product Feature, Price Feature, Place Feature, Promotion, People Feature, Process Feature, and Physical Evidence) on Consumer Purchase Intention. The recommendation is that webcast transactions should continue to be developed and grow, bringing consumers more convenience and benefits and creating many opportunities for more e-commerce businesses. With the continuous innovation of technology, webcast transactions will become more and more intelligent, and there will be more industries to carry out webcasts, providing consumers with more kinds of products to choose from.